Predictive Processing and the Varieties of Psychological Trauma - Wilkinson, Sam; Dodgson, Guy; Meares, Kevin (Frontiers in Psychology, 2017)
A recently popular framework in the cognitive sciences takes the human nervous system to be a hierarchically arranged Bayesian prediction machine. In this paper, we examine psychological trauma through the lens of this framework. We suggest that this can help us to understand the nature of trauma, and the different effects that different kinds of trauma can have. We end by exploring synergies between our approach and current theories of PTSD, and gesture towards future directions.